METHODS OF ORIENTAL SCIENTISTS IN FORMING MUSIC-RHYTHMIC COMPETENCIES IN FUTURE MUSIC TEACHERS - Ibragimova Khonzoda (International Scientific and Current Research Conferences, 2024)
This article is written about music and rhythmic educational tools, their variety, uniqueness, strict regulation of students' activities, specially designed movement, etc.